Rancang Bangun E-Commerce Pada Kip Store Kota Bengkulu Berbasis Web - Raizan Raizan; Venny Novita Sari; Ricky Zulfiandry (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Rapid advances in information technology have driven significant changes in the business world, including in the field of product sales and marketing. KIP Store in Bengkulu City is a business engaged in the sale of various everyday consumer goods; however, it still uses a conventional sales system that is inefficient and has a limited market reach. This research aims to design and develop a web-based e-commerce system for KIP Store to streamline transaction processes, expand marketing reach, and enhance the effectiveness of customer service. The system development method employed is the RAD method, which encompasses the stages of requirements analysis, system design, and implementation. The system was built using the PHP programming language and a MySQL database. The result of this research is a web-based e-commerce application that allows customers to register, search for products, place orders, and make payments online. Based on the results of the testing carried out, this e-commerce system functions effectively and assists KIP Store in managing product, transaction, and customer data more efficiently.